Primary epithelial minor salivary gland tumours: a 20-year retrospective audit of cases in the oral pathology unit at the University of the Witwatersrand, Johannesburg - Mahomed, Yaseer (My University, 2018)
Introduction: Minor salivary gland tumours are uncommon, representing 9 to 25% of all salivary gland tumours. Recent South African reports on the demographics of minor salivary gland tumours are lacking. Aim: The aim is to evaluate the frequency, clinical epidemiology and histological types of minor salivary gland tumours in the Department of Oral Pathology, University of the Witwatersrand from 1997 to 2016. Methods: This cross sectional retrospective audit included a review of the histology reports of all patients diagnosed with benign and malignant major and minor epithelial salivary gland neoplasms. Epidemiologic data including age, gender, site, histologic subtype and incidence for each patient was recorded. The tumours were classified according to the 2005 WHO Classification of salivary gland tumours. Results: There were 553 (2.32%) minor salivary gland tumours, of which 315 (57%) were benign and 238 (43%) malignant. Patients ranged from 9 and 93 years. There was no statistically significant age difference between male and females (p=0.64). Benign tumours occurred much earlier than malignant tumours for both sexes (p=0.00). There was no statistically significant gender difference (p=0.18) for benign and malignant tumours in females (55%; 45% respectively) and males (61%; 39% respectively). The three most common histologic types for both genders were pleomorphic adenoma (52%), adenoid cystic carcinoma (12%) and mucoepidermoid carcinoma (10%). Females were more likely to have malignant tumours than males. The most common sites were the palate (56%) followed by the cheek (11%), lip (9%) and paranasal sinuses (7%). Benign tumours were more prevalent in the palate, and malignant tumours were more prevalent at sites other than the palate (p<0.05). Conclusion: Benign (57%) and malignant (43%) minor salivary gland tumours represent about 2% of the total number of cases diagnosed over the 20-year period. Although the incidence of minor salivary gland tumours was much higher than most previous reports, no overall increase in the number diagnosed per year was observed. Minor salivary gland tumours were more prevalent in females. Benign tumours occurred at a much younger age than malignant tumours. This study serves as a baseline for future studies, especially in South Africa.
A Research Report (Neus7009) submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirement for the degree of Master of Medicine in Otorhinolaryngology (MFOSENTS60), Johannesburg 2018
Keywords: Salivary Gland Neoplasms; Soft tissue tumors